ANALISIS KEPUTUSAN PEMBELIAN PADA TOKO FASHION MAYOUTFIT DI KOTA DEPOK - Muchamad Ferry Adriansyah (2020)
Based on internal data from Mayoutfit Gegerkalong in 2018, Mayoutfit's income has fluctuated in each month, there is an increase in every month and there is also a decrease. This is indicated by Mayoutfit's consumer purchasing decision problematic. So the purpose of this research is to find out, analyze, and prove whether there is an influence of product quality, store atmosphere, and price on purchasing decisions. The method in this study is quantitative with a population that is consumers who have purchased Mayoutfit products in the city of Depok, West Java. Samples taken as many as 75 respondents with purposive sampling method. As well as distributing questionnaires to consumers who have purchased Mayoutfit in the city of Depok during the process of data collection directly through Google Form. The data analysis technique used is descriptive analysis with the analytical tool used is SmartPLS 3.0. The results showed that product quality, store atmosphere, and price had an influence on purchasing decisions for Mayoutfit fashion products in Depok City.